Abnormal electromyographic activity of the urethral sphincter, voiding dysfunction, and polycystic ovaries: a new syndrome?. Issue 6661 (3rd December 1988) - Fowler, C. J.; Christmas, T. J.; Chapple, C. R.; Parkhouse, H. F.; Kirby, R. S.; Jacobs, H. S.
Abstract : A potential association between abnormal electromyographic activity–that is, decelerating bursts and complex repetitive discharges–of the urethral sphincter and difficulty in voiding was examined in 57 women with urinary retention. Abnormal electromyographic activity was found in 33. Ultrasonography of the ovaries in 22 of the 33 women showed that 14 had polycystic ovaries. Of the other eight women, two had had oophorectomies, one had shrunken ovaries and ovarian failure, and one had previously undergone oophorectomy and the other ovary could not be seen; in one neither ovary could be seen, and three had ovaries of normal appearance, although two of these women were taking the contraceptive pill. Thirteen of the group had endocrine symptoms and signs characteristic of the polycystic ovary syndrome. Videocystometrography in 17 of the women who were examined by ultrasonography showed low flow rates and high residual volumes of urine after micturition in 12 women who could void, the other five having chronic urinary retention. A speculative hypothesis for the observed association of impaired voiding, abnormal electromyographic activity of the urinary sphincter, and polycystic ovaries is advanced, based on the relative progesterone deficiency that characterises the polycystic ovary syndrome. Progesterone stabilises membranes, and its depletion might permit ephaptic transmission of impulses between muscle fibres in the muscle of the urethral sphincter, giving rise to the abnormal electromyographic activity. This may impair relaxation of the sphincter, resulting in low flow rates of urine, incomplete emptying of the bladder, and, finally, urinary retention.